Programa de “Educación ambiental” para desarrollar el aprendizaje de hábitos y actitudes de consumo sustentable en niños/as de 5 años en el área de ciencia y ambiente de I.E N°00170 – Naciente de Río Negro - Tomas Espinoza, Jánet Karina (2011)
In the diagnosis and prioritization of the problems encountered in educational institutions often find the lack of habits and attitudes towards sustainable consumption. In the case of School No. 00170 - Rising of Black River, children in early education, they prefer to consume industrial products containing protective plastic bags, rather than natural products, have no educational background to make proper use of products. Faced with this problem, the assumption made was that the program Environmental Education develop significantly the learning of habits and attitudes of sustainable consumption in children of 5 years in the Department of Science and Environment of School No. 00170 - The Rising district of Black River Soplín Elias Vargas in 2011. Furthermore, the objective was to determine that the program of Environmental Education develop learning habits and attitudes of sustainable consumption in children of 5 years in the Department of Science and Environment of School No. 00170 - Rising of Black River's Elias Vargas Soplín district in 2011. The research was applied type of experimental level, pre-experimental design with pretest - posttest and a single group. The sample consisted of 20 children from 5 years enrolled in the lnitial Education Level Educational lnstitution No. 00170 - Black River Rising for District Soplin Elias Vargas in 2011. The data collection instruments were a questionnaire of sustainable consumption patterns and consumer attitudes questionnaire sustainable. These research tools were validated by 5 experts, as considered in the data sheet for each instrument. After analysis of results was determined that the program "Environmental Education" has developed significantly the learning of habits and attitudes of sustainable consumption in children of 5 years in the Department of Science and Environment of School No. 00170 - the Rising Black River District Soplin Elias Vargas in 2011, with t calculated (te: -25.13) than the tabulated value (tt: -1.73).